Integrating design thinking and GEMATH to enhance vocational students’ critical thinking in mathematics - Ismiyati, I'in; Dwijayanti , Ida; Buchori, Achmad (Al-Jabar: Jurnal Pendidikan Matematika, 2026)
Purpose: This study aims to examine the effect of integrating Design Thinking with GEMATH (GeoGebra and MATLAB) on vocational students’ critical thinking skills in mathematics learning. Method: The study employed a quasi-experimental research design using a pretest–posttest control group framework. The participants consisted of 50 eleventh-grade students from a vocational high school in Semarang, Indonesia, selected through cluster random sampling. Students were divided into an experimental group and a control group. The experimental group received mathematics instruction through a Design Thinking approach integrated with GEMATH, while the control group was taught using conventional teaching methods. Data were collected using a critical thinking test developed based on Ennis’ indicators, supported by observation sheets and technology readiness questionnaires. The data were analyzed using normality and homogeneity tests, followed by an independent sample t-test and effect size analysis. Findings: The findings reveal a statistically significant improvement in the critical thinking skills of students who participated in the Design Thinking–GEMATH learning environment compared with those receiving conventional instruction. Significance: The results indicate that integrating Design Thinking with digital mathematical tools can effectively promote higher-order thinking skills and provide an innovative pedagogical strategy for improving mathematics learning in vocational education.